Efecto de las características químicas de dos suelos ácidos a la aplicación de tres enmiendas edáficas - Calero Bravo, Gisella Katiuska (Machala : Universidad Técnica de Machala, 2022)
Acidity is one of the main forms of degradation present in soils and one of the factors that affects crop yields, therefore, in the face of this problem, it is necessary to apply corrective measures of natural or industrial origin, which allow soils to be recovered. acids. The objective of this research was to evaluate the effect of three edaphic amendments (Ca Carbonate, Ash and Biochar of plant origin) on chemical characteristics such as pH, electrical conductivity (EC), organic carbon (CO) and soil organic matter (MOS), from two locations in the Province of El Oro in Ecuador. 297 samples were studied for each locality (L1 and L2) with a completely randomized design (DCA) applying the ANOVA and a Student test (LCD), three types of amendments were used, adding eleven different doses of each amendment with three repetitions per each dose, and samples were evaluated at three incubation times. The analyzes indicated that the use of agricultural lime improved the pH levels in the soils. It was also evidenced that adding ash increased the EC of the soils. The content of CO and OM in the (L1) increased when using agricultural lime and in the same way in the (L2) it was presented in greater amounts when adding Biochar to the soils studied. These materials are an excellent alternative when used as soil amendments, since they correct the chemical properties of the soil, making them suitable for production and improving crop yields.
La acidez es una de las principales formas de degradación presentes en los suelos y uno de los factores que afecta el rendimiento de los cultivos, ante esta problemática es necesario aplicar medidas correctivas de origen natural o industrial, que permitan recuperar los suelos ácidos. El objetivo de esta investigación fue evaluar el efecto de tres enmiendas edáficas (Carbonato de Ca, Ceniza y Biocarbón de origen vegetal) sobre las propiedades químicas como pH, conductividad eléctrica (CE), carbono orgánico (CO) y materia orgánica del suelo (MOS), de dos localidades de la Provincia de El Oro en Ecuador. Se estudiaron 297 muestras por cada localidad (L1 y L2) con un diseño completamente al azar (DCA) aplicando el ANOVA y un test Student (LCD), se emplearon tres tipos de enmiendas, adicionando once dosis diferentes de cada enmienda con tres repeticiones por cada dosis, y las muestras se evaluaron en tres tiempos de incubación. Los análisis indicaron que el uso de Cal agrícola mejoró los niveles de pH en los suelos. También se evidenció que al adicionar Cenizas se incrementó la CE de los suelos. El contenido de CO y MO en la (L1) aumentó al emplear Cal agrícola, mientras que en la (L2) se presentaron mayores valores al emplearse Biocarbón a los suelos estudiados. Estos compuestos tanto químicos como orgánicos son una excelente alternativa al utilizarse como enmiendas edáficas, ya que, corrigen las propiedades químicas del suelo, logrando que éstos sean aptos para producir y mejoren los rendimientos de los cultivos.
Keywords: ACIDEZ DE SUELOS; MEJORA DE PRODUCTIVIDAD; MEDIDAS CORRECTIVAS